EMPOWERING THE DAYAK COMMUNITY’S ECONOMY THROUGH DIGITAL MARKETING OF TRADITIONAL ACCESSORIES VIA SOCIAL MEDIA - Heni Ermewaningsih (Multidisiplin Pengabdian Kepada Masyarakat, 2025)
Rural communities in Kalimantan, particularly the Dayak tribe, possess inherited skills in creating unique accessories, ornaments, and traditional Dayak clothing. However, these products have not been developed or widely introduced to the public due to limited technological knowledge and modern marketing strategies. This has resulted in the underutilization of the cultural and economic potential of the Dayak community. This community service aktivity aims to assist the Dayak people in utilizing social media technology as a means of marketing their accessory products. The strategies implemented include training in the use of social media platforms such as Facebook, Instagram, and WhatsApp Business, creating attaractive and high-quality promotional content, and providing assistance in sustainable social media account management. Through this program, the community is expected to introduce Dayak traditional accessories to a wider market, increase product selling value, expand their customer network, and foster economic independence. The results show improved participants’ skills in promotional content creation, understanding social media algorithms, and gaining confidence to market their products online. This social media utilization strategy is proven effective in optimizing the marketing of Dayak rural accessories and can be a model for implementation in other indigenous areas of Indonesia.